Sex-Related Difference in Nitric Oxide Metabolites Levels after Nephroprotectant Supplementation Administration against Cisplatin-Induced Nephrotoxicity in Wistar Rat Model: The Role of Vitamin E, Erythropoietin, or N-Acetylcysteine. (11th March 2013) - Nematbakhsh, Mehdi; Pezeshki, Zahra
Abstract : Background . Nitric oxide (NO) concentration in serum is altered by cisplatin (CP), and NO influences CP-induced nephrotoxicity. The effect of nephroprotectant agent supplementation (vitamin E, human recombinant erythropoietin (EPO), or n-acetylcysteine (NAC)) on the NO metabolites levels after CP administration in the two genders was determined. Methods . Sixty-four adult Wistar rats were randomly divided into 10 groups. Male and female rats in different groups received vehicle (saline), CP (7 mg/kg) alone, CP plus EPO (100 IU/kg), CP plus vitamin E (250 mg/kg), and CP plus NAC (600 mg/kg). CP was administrated as a single dose, but the supplementations were given for a period of 7 days. Results . In male rats, the serum levels of total NO metabolites (NO x ) and nitrite were increased significantly (P < 0.05 ) by CP. However, vitamin E significantly reduced the serum levels of these metabolites, which was increased by administration of CP (P < 0.05 ), and such findings were not observed for female rats. The EPO or NAC did not influence NO metabolites neither in male rats nor in female rats. Conclusion . Although vitamin E, EPO, and NAC are reported to be nephroprotectant agents against CP-induced nephrotoxicity, only vitamin E could reduce the level of all NO metabolites only in male rats.